The Essence of Female Journalist’s Experience In the Newsroom of Pakistan - Ahmed, Jamshaid; Hasfi, Nurul; Sunarto, Sunarto (Ikatan Sarjana Komunikasi Indonesia, 2024)
This study delves into the challenges confronted by women working in the media sector in Pakistan, specifically focusing on journalists, producers, and editors. The primary objective is to identify and analyze the various obstacles hindering the professional advancement and well-being of women in this industry. Phenomenology method was used to collect the data. Thematic analysis was employed to identify common themes and patterns across the participants' experiences and perceptions. The findings reveal a multitude of challenges faced by women in the media industry, including workplace stress, technical difficulties, tight deadlines, gender discrimination, biased promotion practices, unequal pay, harassment, limited training opportunities, and closed circles obstructing career progression. Gender inequalities are pervasive, with women being underrepresented in top management positions and facing lower compensation compared to their male counterparts. Additionally, female journalists struggle to balance work and personal life responsibilities amidst societal expectations. Â To address these challenges, the study recommends the implementation of policies and regulatory frameworks to protect women journalists, the establishment of training programs for professional development, the creation of mentorship opportunities, and the promotion of inclusivity and diversity within media organizations. Collaborative efforts between governments, media outlets, and society are essential to ensure the safety, well-being, and advancement of women in the media sector.